2021
DOI: 10.1111/odi.13865
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms in odontogenic keratocysts and ameloblastomas: A systematic review

Abstract: Objectives:The aim of this systematic review was to critically analyze available data on gene polymorphisms in odontogenic keratocysts (OKC) and ameloblastomas, including their possible relationship with clinical and histological features of these lesions. Materials and Methods: A comprehensive search of Web of Science Scopus, PubMed, Cochrane Central Register of Controlled Trials and EMBASE was conducted using relevant key terms and supplemented by a gray literature search. Quality assessment of included stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The score obtained was expressed as a percentage ([points obtained/maximum points] × 100). Finally, the percentage was taken as a reference to classify the studies as high (>80%), moderate (50–80%), or low (<50%) quality, as reported in previous studies [ 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The score obtained was expressed as a percentage ([points obtained/maximum points] × 100). Finally, the percentage was taken as a reference to classify the studies as high (>80%), moderate (50–80%), or low (<50%) quality, as reported in previous studies [ 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The STREGA checklist for case‐control studies includes 49 items, five of which are related to both cases and controls information. The STREGA score for each study was expressed as the percentage of the number of questions adequately reported in the study divided by the number of applicable questions 34 . According to the STREGA score, studies were categorized into high (>80% of the STREGA criteria achieved), moderate (50%‐80% of the STREGA criteria fulfilled), or low (<50% of the STREGA criteria met) quality level.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of each study was assessed by Newcastle-Ottawa quality assessment scales (NOS), 32 adequately reported in the study divided by the number of applicable questions. 34 According to the STREGA score, studies were categorized into high (>80% of the STREGA criteria achieved), moderate (50%-80% of the STREGA criteria fulfilled), or low (<50% of the STREGA criteria met) quality level.…”
Section: Quality Evaluationmentioning
confidence: 99%
“…The participation of metalloproteinases (MMPs, as MMP-1, MMP-7, MMP-9, MMP-13, and MMP-26) in the biological behavior and invasion mechanisms of OKCs lesions has been demonstrated in many articles [ 6 , 7 , 8 , 9 , 10 ]. They can modify the structural and functional components of the extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%